LINDA - Longitudinal INdividual DAta for Sweden - Per-Anders Edin; Peter Fredriksson (Uppsala University, Department of Economics, 2000)
This paper presents LINDA - a register-based longitudinal data set for Sweden. LINDA consists of a large panel of individuals, and their household members, which is representative for the population during the period 1960 to 1998. As future years become available, this information will be added to the data set. LINDA also includes a specific sample of immigrants. This sample has the same design and covers the same time period as the population sample. We provide a description of the sources of data, the sampling frame as well as the sampling procedure. Moreover, to illustrate the usefulness and particular features of LINDA, we give the development of some of the key variables in the data set.
urn:nbn:se:uu:diva-2500
Keywords: D10; D30; H31; J15; J60; 330; Longitudinal data; Population sample; Immigrant sample; Sweden; Panel; Zeitreihenanalyse; Schweden; Laufende Stichprobenerhebung